Perception, precausions and acceptance of vaccination against SARS COV-2 viral infection among health workers in two tertiary hospitals in southeast Nigeria, four years after the onset of the pandemic - Nwali, Matthew Igwe; Immaculata, Nwali Nneka; Donald, Nweze John (International journal of health sciences, 2023)
Background: The study was conducted in two tertiary hospitals located in ababkaliki the capital city of Ebonyi State. Aim: To ascertain the perception, awareness and vaccination of COVID-19 among the health workers. Methods: A questionnaire/data sheet was developed for the study. Information on sociodemographic characteristics, perception and awareness and COVID 19 vaccination were obtained. The data were fed into the computer using SPSS version 25, Illinoi USA and analysis done. Results: We had 420 respondents with the mean age of 39.1±9.8 and ranged from 20 to 70years made up of doctors, nurses/midwives, laboratory scientists, pharmacists and others. There was high awareness of COVID 19 in the group but with poor knowledge of spread 47.4% and preventive measures 43.1%. awareness of vaccine was high 96.9% but the uptake was low 33.8% with major reason being fear of side effect and some also believe vaccine is a scam. Some of the respondents were survivors of COVID 19. Conclusion: There is high awareness of COVID 19 disease in the hospitals but poor knowledge of mode of spread and preventive measures including very low uptake of anti-COVID 19 vaccines and inadequate provision of PPEs 4 years after the onset of the pandemic.